1985
DOI: 10.7326/0003-4819-102-4-490
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren's Syndrome After Infectious Mononucleosis

Abstract: A healthy young woman developed primary Sjögren's syndrome after protracted infectious mononucleosis. The diagnosis of primary Sjögren's syndrome was supported by histologic evidence of sialadenitis in labial salivary glands, rheumatoid factor, hypergammaglobulinemia, the HLA-B8 phenotype, and a high titer antibody to the anti-La (SS-B) nucleoprotein that co-precipitated the small ribonucleic acids encoded by Epstein-Barr virus, EBER 1 and EBER 2, as well as "host" RNA. There was strong humoral immunity to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(25 citation statements)
references
References 14 publications
2
21
0
2
Order By: Relevance
“…Several previous studies (26)(27)(28)(29) have implicated EBV in other types of autoimmune diseases. Most rheumatoid arthritis patients (70-90%) have antibodies directed against the rheumatoid arthritis precipitant, which is an antigen extracted from EBV-infected cells, and >90% of the patients have antibodies to the rheumatoid arthritis nuclear antigen (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies (26)(27)(28)(29) have implicated EBV in other types of autoimmune diseases. Most rheumatoid arthritis patients (70-90%) have antibodies directed against the rheumatoid arthritis precipitant, which is an antigen extracted from EBV-infected cells, and >90% of the patients have antibodies to the rheumatoid arthritis nuclear antigen (26).…”
Section: Discussionmentioning
confidence: 99%
“…Most rheumatoid arthritis patients (70-90%) have antibodies directed against the rheumatoid arthritis precipitant, which is an antigen extracted from EBV-infected cells, and >90% of the patients have antibodies to the rheumatoid arthritis nuclear antigen (26). Some patients with acute polyarthritis were also found to have EBV (27)(28)(29). Thus, in addition to ND-associated diseases, EBV may be involved directly or indirectly in several types of autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…They also have decreased EBVspecific T-cell cytotoxicity [55] which accounts for the impaired ability to abort in-vitro outgrowth in regression assays of EBV-induced B-cell transformation [54,55]. Decreased EBV-specific T-cell cytotoxicity might be explained by the reported decrease in MHC class I expression on B cells of patients with Sjögren's syndrome [37].…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…There is increasing evidence suggesting that EBV infection may be related to lacrimal gland lymphocytic proliferation of Sjögren syndrome, which leads to decreased aqueous tear production and severe DED (40,41) . Many studies have reported primary Sjögren syndrome development immediately after serological confirmation of infectious mononucleosis (42)(43)(44) .…”
Section: Hepatitis Cmentioning
confidence: 99%